PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DALAM MENILAI KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN DI INDONESIA - Ratih Wulan Asri; Yulianti . (STIE Pelita Nusantara Semarang, 2014)
This research examines the effect of corporate governance mechanism towards earnings management to evaluate financial performances of banking industries in Indonesia. This research use purposive sampling method in banking industries listed in Indonesia Stock Exchange from 2008 until 2012. Research sample consist of 14 banking companies. This research use multiple regression method. Dependent variable is financial performances, independent variable is corporate governance mechanism, and intervening variable is earnings management. The result of this research shows that (1) corporate governance mechanisms towards earnings management are having significant influence only for insitusional ownership proxy, (2) earnings management are not having significant influence towards financial performances, (3) corporate governance mechanisms that intervened by earnings management are not having significant influence toward financial performances.